Characteristics of Effective English Language Teachers: Student and Teacher Perspectives at a Thai University - Adriano Quieti (2022)
This study investigated students’ and teachers’ perceptions of the characteristics of effective English language teachers in the Thai cultural context. A survey comprising 68 Likert-scale items was administered to students (n = 124) and teachers (n = 11) in the intensive English program (IEP) of a Thai university. The survey measured the participants’ perception of the characteristics of effective teachers in seven areas: general characteristics, affective variables, knowledge about students, pedagogical knowledge, content knowledge, knowledge about classroom management, and professional development. A comparison of the responses showed a statistically significant difference between the median responses of teachers and students in three areas: affective variables, knowledge of students, and professional development. In all three areas, students ascribed a higher level of importance. These findings have implications for teachers, who may underestimate the value that their students place on the personal and affective aspects of education and on professional development.